Adjustment to maximal work intensity during interval swimming using various work:rest ratios - Troup, J. P.; Barzdukas, A.; Trappe, S. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
While the duration of work will affect the relative energy contributions during work of an interval type, little is known of the role of the rest duration during interval work. The purpose of this study was to determine what effect varying the work:rest ratio has on the energy contributions when the work duration and intensity are kept constant. Well trained swimmers participated in a series of interval work sets of 12 x 100 m freestyle swims at each of the following work:rest ratios, 1:2, 1:1 and 1:1/2. All tests were conducted on separate days. During each swim, accumulated 02 uptake was measured to describe the percent aerobic contributions. Additionally, accumulated 02 deficit was calculated in order to describe the anaerobic profile of each swimming set. From the accumulated 02 uptake data, the rate of adjustment to 25% of total energy demand was determined for each workout set interval. Blood lactate and base excess for all work repeats were also measured. The data suggest that (1) the rate of adjustment is faster when the work:rest ratio is shorter, (2) at a given distance, a short rest interval results in a higher aerobic contribution and (3) longer rates of adjustment reflect a greater anaerobic contribution.